Strategi Guru Fikih dalam Mengatasi Problematika Pembelajaran Fikih di MTsN 2 Kota Palangka Raya - Anton Saputra; Noorazmah Hidayati; Nadia Azizah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to describe and analyze the strategies employed by fiqh teachers in addressing fiqh learning challenges at MTsN 2 Palangka Raya. A qualitative approach with a holistic single-case study design was employed. Data were collected through interviews with one fiqh teacher and three students, participant observation, and document analysis. Data analysis followed the Miles, Huberman, and Saldaña (2014) model. The study identified five main strategies: (1) self-regulated learning, (2) contextual teaching and learning, (3) motivational strategy, (4) environmental change strategy (learning in gazebos and mosques), and (5) individual oral testing strategy. A perception gap between teachers and students regarding the use of technological media was also revealed. Supporting factors include madrasah support and availability of basic facilities, while inhibiting factors include limited projector access, scheduling conflicts, limited teacher digital readiness, and low student intrinsic motivation. The strategies implemented are adaptive and contextual, but their effectiveness remains limited due to systemic and personal factors..